Contextualising the bycatch 'problem' in the Olifants Estuary Small-Scale Gillnet Fishery using an Ecosystem Approach to Fisheries - Rice, Wayne Stanley (Department of Environmental and Geographical Science, 2016)
Conventional fisheries management approaches have been shown, in many instances, to have been ineffective in dealing with complex conservation concerns such as bycatch. Greater considerations for broader-scale and holistic approaches, as proposed by the 'Ecosystem Approach to Fisheries' (EAF) and the 'balanced harvesting approach', are beginning to challenge some of the negative misconceptions around bycatch, especially in small-scale fisheries. The need for a more holistic approach to fisheries management, particularly in small-scale fisheries, in South Africa is highlighted by its commitment to an EAF and the recent Small-Scale Fisheries Policy, for which the Marine living Resource Act of 1998 provides the legal framework to implement. The case study of the Olifants estuary small-scale traditional gillnet fishing community, located on the west coast of South Africa, provides a particularly relevant example of a complex fishery requiring a holistic approach. Current regulations prohibit the harvesting or retention of any bycatch species. Fisheries management worldwide and in South Africa, generally view gillnet fisheries as destructive, due to the occurrence of bycatch and the fact that many of these bycatch species are considered overexploited, which has led to numerous attempts over the years to phase out the Olifants gillnet fishery. The purpose of this study was to, firstly, use an EAF framework to contextualise the issue of bycatch in the Olifants gillnet fishery, and secondly, to identify the relative contributions of all fisheriy sectors to the four key selected linefish species caught as bycatch by the fishery. An extensive review and analysis of available secondary data, as well as primary data collected for this study, have estimated, with acknowledged limitations, the magnitude of the exploitation by all known fisheries of these species. Key information from small-scale fisher interviews and community-monitoring data highlight the capture rate of key linefish species by this fishery. This is echoed by recent landings for 2012 indicating the relative contribution of the national beache seine and gillnet fishery to the overall catch of (Elf [Pomatomus saltatrix] - 26.94%; Silver Kob [Argyrosomus inodorus] - 0.88%; White Stumpnose [Rhabdosargus globiceps] - 1.05% - excluding the recreational sector). A significant finding of this study is the substantial levels of cross-sectorial exploitation of Silver Kob and White Stumpnose, and to a somewhat lesser extent Elf and White Steenbras.